The Internalization of Democratic Values Through Social Studies Learning at MA Islamiyah Senori Tuban - Anggraeni Ratridite Sudarso; Rifai Rifai; Faridatul Lailiyah; Deni Pratiwi (Journal of Social Studies Education and Humanities Research, 2024)
This study aims to analyze the cultivation of democratic values such as responsibility, tolerance, and participation. The research employs a descriptive qualitative method, with data collected through interviews. The subjects of this study are 11th and 12th-grade students at MA Islamiyah Senori Tuban. Based on the findings, it can be concluded that active learning methods, such as group discussions and social studies presentations, effectively instill democratic values in students